Neutrophils in ANCA-associated vasculitis: Mechanisms and implications for management - Ge, Shangqing; Zhu, Xingyu; Xu, Qinyao; Wang, Junyan; An, Cheng; Hu, Ying; Yang, Fan; Wang, Xinyi; Yang, Yipin; Chen, Shuwen; Jin, Ruimin; Li, Haiyan; et al. (Frontiers in Pharmacology, 2022)
Antineutrophil cytoplasmic antibody (ANCA)-associated vasculitis (AAV) is a kind of autoimmune disease involving multiple systems of the whole body, which is characterized by small vasculitis and pathogenic ANCA. These include granulomatous polyangitis (GPA), microscopic polyangitis (MPA), and eosinophilic granulomatous polyangitis (EGPA). ANCA is an autoantibody targeting the cytoplasmic components of neutrophils and monocytes. It can be divided into cytoplasmic ANCA (cANCA), perinuclear ANCA (pANCA) and atypical ANCA. Activated neutrophils close to endothelial cells are considered to be the cause of AAV injury. The cytoplasm of neutrophils includes a huge number of granule-like proteins, the most significant of which being proteinase 3 (PR3) and myeloperoxidase (MPO). This review examines the association between neutrophils and various types of antineutrophil cytoplasmic antibody (ANCA)-associated vasculitis (AAV) and emphasizes recent research on neutrophil control. The underlying signaling pathways and possible clinical significance of neutrophils in AAVs are described in detail, implying that they might be used as an epigenetic biomarker and therapeutic target for these AAVs